Thermo-responsive self-healing polycaprolactone urethane coatings from waste palm cooking oil - Zain N.M.; Ghazali F.A.; Ali E.S. (Blue Eyes Intelligence Engineering and Sciences Publication, 2024)
Indexed by Scopus